Overview of Islamic Economics About the Practice of Cultivating Plantation Land With a Land Wage System - Zaenal Abidin (STIE Syari'ah Al-Mujaddid Tanjung Jabung Timur, 2022)
The purpose of this research is to reveal the problems; How is the practice of cultivating plantation land with a profit-sharing system in Koto Kandis? How is the Islamic economic review of the practice of cultivating plantation land with a profit-sharing system in Koto Kandis? This type of research uses qualitative research with a descriptive approach. Based on the results of the discussion and analysis, conclusions were drawn: First, the implementation of the practice of cultivating plantation land with a profit-sharing system in Koto Kandis Village, was carried out in three stages, Second, an Islamic economic review on the practice of cultivating plantation land with a profit-sharing system in Koto Kandis village, according to an Islamic economic review is permissible in Islam, and is recommended with the principle of mutual cooperation in goodness.